Тиазолохиназолиноны и тиазолотиенопиримидиноны -антиоксиданты и ингибиторы открытия митохондриальных пор - Зборовский, Ю.Л.; Орысык, В.В.; Васькевич, Р.И.; Станинец, В.И.; Шиманская, Т.В.; Добровольский, Ф.В.; Сагач, В.Ф. (Журнал органічної та фармацевтичної хімії, 2008)
Показана способность функционально замещенных тиазолохиназолинонов и тиазолотиенопиримидинонов повышать эффективность кислородного обмена сердца и оказывать протекторное действие на функцию сердца в условиях ишемии-реперфузии вследствие угнетения образования митохондриальных пор. Показана здатність функціонально заміщених тіазолохіназолінонів та тіазолотієнопіримідинонів збільшувати ефективність кисневого обміну серця та здійснювати протекторну дію на функцію серця в умовах ішемії-реперфузії внаслідок пригнічення утворення мітохондріальних пор. It has been shown that ischemia-reperfusion disturbances of the heart function were decreased and the oxygen metabolism was normalised in animals treated with the functionally substituted quinazolinones and thiazolothienopyrimidinones comparing to the non-treated control. One of the mechanisms of the cardioprotective effect of these compounds could be inhibition of mitochondrial permeability transition pore opening during ischemia-reperfusion of the heart.